2022
DOI: 10.1177/00222194211065499
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Use of Evidence-Based Tier 1 Literacy Practices That Benefit Students With Disabilities

Abstract: The adoption and sustainability of evidence-based Tier 1 literacy practices in secondary content-area classes is important to improve the reading success among students with learning disabilities. We conducted an exploratory multiple-case study investigating teachers’ adoption and sustained use of evidence-based Tier 1 literacy practices that benefit students with learning disabilities. The study was conducted within the context of an adolescent literacy model demonstration project funded by the Office of Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Collaboration among administrators and departments of special education and literacy at the school or district level may be necessary so that coaches and assistant principals are prepared to support teachers’ implementation of evidence-based literacy instruction in content-area classes for students with and without disabilities. Such coaching collaborations should also target co-teaching to maximize the effectiveness of this service delivery model (e.g., Wexler et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaboration among administrators and departments of special education and literacy at the school or district level may be necessary so that coaches and assistant principals are prepared to support teachers’ implementation of evidence-based literacy instruction in content-area classes for students with and without disabilities. Such coaching collaborations should also target co-teaching to maximize the effectiveness of this service delivery model (e.g., Wexler et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Administrators can take this support a step further by encouraging teachers to work with coaches and providing coaches with time and resources to facilitate coaching (Calo et al, 2015; Gross, 2012). In fact, Wexler et al (2022) found that designated administrators in schools that sustained a schoolwide middle school literacy model (a) clearly set expectations for teachers to use the target set of evidence-based literacy practices, (b) participated in PD efforts, such as reviewing the content of PD, and (c) allowed coaches to become fully embedded in their schools. These findings align with those of Rush (2013), who examined 26 secondary literacy coaches’ perspectives on the impact of sufficient and insufficient administrator support.…”
Section: What Do We Know About Secondary Literacy Coaching Today?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, for this interest, this does not turn out to be a critical factor in the teacher-student rapport but rather the pertinent strategies deployed to meet a high quality educational output. Notwithstanding student learning differences, educators can deploy from performance evidence a learning student-centred framework relied on the underlying surroundings-linked factors on childhood learning conditions, attaching those learning barriers through practice [65].…”
Section: Teacher-student Bonds As a Moulding Communication Skills Factormentioning
confidence: 99%
“…Next, I built rapport with teachers so that they used me as a resource , namely in the role of a mentor or literacy coach (Wexler et al, 2021). Teachers were encouraged to seek help in developing lesson plans, finding materials, and customizing our sessions to meet their needs.…”
Section: The Write Principlesmentioning
confidence: 99%